Orthogonally polarised shear waves for evaluating anisotropy and cracks in metals. (July 2021) - Parra-Raad, Jaime; Lan, Bo; Cegla, Frederic
Abstract: The detection of crack-like defects using ultrasound is a problem widely studied by the non-destructive evaluation community. In this work, a technique of how to detect the presence of a crack-like defect and estimate its orientation in an anisotropic material by means of two orthogonal shear waves is presented. A detailed study of shear wave propagating and splitting at any incident angle, and its interaction with crack-like defects in anisotropic materials, is also presented. In this paper it is shown that by the use of two orthogonal shear waves with linear polarisation the authors could: 1) estimate the material level of anisotropy within approximately 0.5 % of the measured value; 2) estimate the angular position of the principal shear directions of the material with respect to the orthogonal shear wave sources within ± 5 ∘ accuracy; 3) excite a shear wave purely polarised along one of the principal shear directions with two orthogonal shear waves placed at an arbitrary angular position; 4) detect the presence of a crack-like defect in an anisotropic material based on the back-wall echoes of two orthogonal shear waves, 5) estimate the orientation of a crack-like defect in an anisotropic material within ~ ± 5 ∘ of the theoretical value. The simulation and experimental results obtained show that the technique presented in this paper has potential to become an effective tool for crack-like defect detection and material characterisation.